Strategic Framework of Air Traffic Development - Steiner, Sanja; Galović, Borivoj; Radačić, Željko (Promet - Traffic&Transportation, 2008)
The paper elaborates the past development of air traffic inEurope from the aspect of its economic benefits and ecologicallack of sustainability of conventional technology. The mainguidelines of the strategic development are related to the implementationof the global ecological standard and actual reformationprocesses of the air traffic management system postulatedby A TM 2000+ Strategy and the ’Single European Sky’standard. The paper studies the wider aspects of integrated trafficdevelopment at the regional level and the factors influencingfurther development of the European air traffic.